Shockwave and Non-transfemoral Transcatheter Aortic Valve Replacement - Eden C Payabyab (US Cardiology Review, 2021)
Transcatheter aortic valve replacement (TAVR) has become a widely adopted treatment modality for severe aortic stenosis. Transfemoral access is the approach of choice; however, approximately 25% of patients undergoing TAVR also have concomitant peripheral arterial disease. The recent advent of intravascular lithotripsy has enabled preservation of transfemoral access in some patients; although, a proportion still require alternative, non-femoral access. Alternative access sites can be broadly categorized into transthoracic and peripheral, facilitated by surgical or percutaneous techniques. In this review, the technical details and clinical outcomes of various TAVR accesses are discussed. Initially, transthoracic approaches were most common, but recently, the trend has been toward alternative peripheral access due to superior outcomes. Although there are no randomized data to support all the alternative access sites, the experiences reported provide available options for a large portion of patients to be candidates for TAVR. The intervention site should be selected by a multidisciplinary heart team based on patient anatomical factors and institutional expertise.